Ponding Calculations in LRFD and ASD - Carter, Charles J.; Zuo, Jiahong (Engineering Journal, 1999)
The definitions of stress indexes in the 1993 LRFD Specification and the 1989 ASD Specification do not result in similar designs. A modification is suggested for the definitions of the stress indexes in AISC LRFD Appendix K2 to eliminate this anomaly. Simplified equations for the flexibility constants Cp and Cs suggested by Milbradt are also validated for preliminary design.